Lo & behold - Mass, Wendy, 1967- (Random House, 2023)
After her mother leaves the family, twelve-year-old Addie Brecker's life is thrown into turmoil. To distract them from the problems at hand, her father takes her with him on a six-week stint to Spring Haven University where he'll be working on a virtual reality project with students. There, she meets new friend Mateo Vargas, who helps her beta-test the programs. Through the alternate worlds, Addie discovers ways to cope and understand what she's feeling, and also realizes that she's been avoiding the real world and must find a way to let others in.